Influence factor and mechanism of FLASH effect - Feng, Tingyu; He, Tianyang; Ye, Wentao; Xiang, Lisha (Frontiers in Oncology, 2025)
FLASH radiotherapy (FLASH-RT) represents an innovative treatment modality utilizing ultra-high dose-rate irradiation (>40 Gy/s). The FLASH effect, induced by FLASH-RT, is characterized by the selective radioprotective effect of normal tissue while preserving tumor control efficacy. Currently, FLASH effect has been confirmed in many preclinical studies and clinical studies. However, the mechanism and the influencing factors of FLASH effect remain ambiguous. This review systematically summarizes current understanding of the mechanism and influencing factors of FLASH effect, providing theoretical basis for the future study and application of FLASH-RT.